The Significance of Pragmatic Competence in English Language Teaching: Behdini Kurdish University Teachers’ Perspectives (Raparin Journal of Humanities (RJH), 2025)
Pragmatics concerns the indirect meaning that needs context and, sometimes, knowledge of the target language’s cultural norms to be interpreted. Thus, the present study sheds light on pragmatic competence and its importance in EFL classrooms from the point of view of Behdini Kurdish university teachers. Twenty-five teachers responded to the open-ended and agreement statements survey. The questions that the present study addressed were: whether Behdini Kurdish university teachers are familiar with pragmatics and speech acts or not and whether they agree that pragmatic competence needs to be implemented in the EFL curriculum or not. The data was analyzed both qualitatively and quantitatively in terms of the content of the teachers’ responses to the open-ended questions, and also the numbers and percentages of the agreement statements. The results revealed that Behdini Kurdish university teachers are aware of pragmatics, speech acts, and eventually pragmatic competence. They also indicated that the teachers are familiar with the inappropriate topics that need to be avoided in cross-cultural settings. Finally, the study recommends that pragmatic competence should be implemented and tested in EFL classrooms, and teachers can help their students develop their pragmatic awareness in the target language.